Pepper powder marketing training in Salo Palai Village, Muara Badak District, Kutai Kartanegara Regency - Ratna Wulaningrum; Amiril Azizah; Dita Andansari (Universitas Muhammadiyah Magelang, 2021)
Salo Palai Village is one of the villages in Kutai Kartanegara Regency, East Kalimantan which has the superior commodity of pepper 'Malonan'. Pepper land in Salo Palai Village reaches 169 ha with a productivity of 1.9 tons/ha. The pepper harvest is sold in granular form at a price of IDR 30,000.00/kg and there is no product diversification, such as pepper powder. This is what makes there is no increase in the selling value of pepper that has been produced by farmers. Community service activities in the marketing of powder pepper are expected to be an effort to provide an understanding of the importance of product diversification as an effort to increase selling value. The methods used are tutoring and training. This activity results the pepper powder products in packaged bottles with labels, which are expected to increase values.